A Novel Missense Variant in the AGRN Gene; Congenital Myasthenic Syndrome Presenting With Head Drop. Issue 3 (March 2017) - Karakaya, Mert; Ceyhan-Birsoy, Ozge; Beggs, Alan H.; Topaloglu, Haluk
Abstract : Abstract: Congenital myasthenic syndromes (CMS) are a heterogeneous group of diseases of the neuromuscular junction caused by compromised synaptic transmission. Clinical features include early-onset weakness of limbs and oculobulbar muscles resulting in hypotonia, bulbar paresis, ptosis, and hypoventilation. The first dropped head syndrome in children were detected in 2 patients with LMNA and SEPN1 mutations. We report a 17-month-old boy with dropped head and limb–girdle weakness, who had no ptosis or ophthalmoplegia at presentation. We performed whole exome sequencing, which revealed a homozygous missense variant in the AGRN gene c.5023G>A, p.Gly1675Ser in the LG2 domain, which is predicted to be likely disease causing by in silico tools. Agrin is known to play a critical role in the development and maintenance of the neuromuscular junction. Agrin-related CMS is one of the rarest subtypes. Of note, our patient is the first described patient with agrin-related CMS with dropped head phenotype.